Beyond scale to efficiency: a dual-perspective framework for green finance in China - Ren Wang; Yicheng Duan; Danchen Li (Discover Sustainability)
Abstract As a crucial policy instrument for low-carbon transition, green finance needs to achieve efficiency improvements while promoting scale growth, making efficiency evaluation particularly necessary. This study proposes a multidimensional analytical framework that incorporates both technical efficiency (input–output analysis) and allocation efficiency (resource flows within/between industries), conducting empirical tests based on China's micro-level enterprise and provincial aggregate data. Through temporal trend comparisons and spatial correlation analysis, the study finds: (1) The technical efficiency of China's green industries generally shows a steady upward trend in technical efficiency, while the allocation efficiency of green finance among and between industries shows an overall fluctuating upward trend; (2) The rate of convergence in allocation efficiency within the green finance industry across different regions is much faster than that between industries, suggesting that reallocation of financial resources among industries faces greater obstacles; (3) Inter-industry allocation efficiency of green finance exhibits a more significant positive spatial autocorrelation than within-industry allocation efficiency, elucidating the impact of local government's strategic interaction behavior on green finance development; and (4) The spatial correlation of inter-industry allocation efficiency in green finance is less than that of within-industry allocation efficiency, yet it is more closely associated with the technical efficiency of the green industry, signifying that local financial resource competition affects the efficiency of green finance development. Therefore, to foster high-quality green finance development, attention should be given to establishing a multidimensional linkage system, creating a multi-layer compatible spatial pattern for green finance, exploring diverse interaction drivers for green finance development, and establishing a multi-party linkage model for green finance development.